Supuestos de validez de la compraventa de bien inmueble ajeno en el Derecho Civil Peruano - Zavaleta Sedano, Martin Eduardo (2019)
ABSTRACT The present investigation is directed to determine if based on the current norms, it can be considered that a contract of sale on real estate of others, would find legal protection by our civil legislation. It does not seek to question whether the way it is regulated is fair or not, or if this regulation is adjusted to international standards, that is, if it is similar to the regulation that other countries in our system and legal tradition make on the matter. The purpose of this investigation is only to determine if, as this figure is regulated in the current regulations, it is correct or not to consider a contract of this type valid. One of the main purposes of having carried out this investigation was to conclude on a clear idea regarding the treatment that should be given to this type of contract, since our judiciary has been expressing arguments and positions that differ greatly in relation to the interpretation made by the generality of the national doctrine. The attempt to reconcile these positions, finding a solution that leads us to assume a single position with respect to the supposed configurators of this contract, was one of the aims that was intended to be achieved with the present investigation. For this purpose, the study of the different arguments contributed by the national doctrine was carried out, applying the scientific method and the analysis of the common points, confronting ideas of being the case. In the same way, judgments issued by the Supreme Court were analyzed, in order to know the position it assumes on the matter, to then confront these arguments with the current regulations and, through the exegetical method, determine whether the interpretation of the articles brought collate, they are correct in light of our right as a whole, making a systematic interpretation of them. Finally, and after the aforementioned analysis, it was obtained as a main result, to consider that a contract for the sale of third-party real property, like any contract, is in principle a source of obligations, not containing by itself, grounds for nullity. In the same way, it was determined that our Supreme Court limits the figure of the contract for the sale of a foreign property to the assumption in which both celebrant parties know about the alienation and where one of them is only obliged to obtain that the other acquires, qualifying the other cases as configurators of the ‘estelionato’ criminal type, figure that has another typical structure, which cannot be compared to the civil contract under study. Likewise, it was determined as one of the delimiting elements to find us in front of a authentic sale of other people's property, and therefore valid for the right, that of the necessary postponement of the real effect of the contract, that is, the verification at a later moment of the transfer property, as explained and detailed in the present investigation. The main conclusion arrived at is that, under the Peruvian civil law, in its legal and doctrinal sources, the contract of sale of third-party real property is valid, since it is a contract that contains all the presuppositions, elements and requirements of validity of the act legal, not being one of them, the legitimacy to dispose.